PENGARUH REMUNERASI, FREKUENSI RAPAT DEWAN DAN PROFITABILITAS TERHADAP RISIKO PEMBIAYAAN PERBANKAN SYARIAH INDONESIA DENGAN ISLAMIC SOCIAL REPORT SEBAGAI MODERASI - Muhammad Tamul Fikri; Fikri Hidayat; Zamah Sari (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to examine the effect of board remuneration, frequency of board meetings and profitability on financing risk with Islamic social report as a moderating variable. The data used in this research is secondary data. The population in this study are Islamic commercial banks registered with the Financial Services Authority (OJK) and Bank Indonesia during 2017-2021. The sample was selected using purposive sampling method and obtained 14 banks each year. The number of samples used in this study were 9 banks. The analysis test uses panel data regression analysis. The results in this study indicate that the remuneration of the board of commissioners has no effect on financing risk, the frequency of board of commissioners' meetings has a negative effect on financing risk, the remuneration of the board of directors has a negative effect on financing risk, the frequency of board of directors meetings has a positive effect on financing risk, remuneration of the sharia supervisory board has a positive effect. on financing risk, the frequency of sharia supervisory board meetings has a positive effect on risk and profitability has no effect on financing risk. Then for Islamic social reporting, it can strengthen the relationship between the remuneration of the board of commissioners, the remuneration of the board of directors, the remuneration of the sharia supervisory board, the frequency of the board of directors meetings and the frequency of the meetings of the sharia supervisory board as well as profitability to financing risk and cannot moderate the relationship between the frequency of the board of commissioners' meetings and the financing risk. Keywords: Remuneration, Board Meetings, Profitability, Financing Risk, Islamic Social Report